2008
DOI: 10.4049/jimmunol.181.7.4723
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin 3 Mediates Endocytosis of CCR7 following Ligation of CCL19 but Not CCL21

Abstract: Internalization of ligand bound G protein-coupled receptors, an important cellular function that mediates receptor desensitization, takes place via distinct pathways, which are often unique for each receptor. The C-C chemokine receptor (CCR7) G protein-coupled receptor is expressed on naive T cells, dendritic cells, and NK cells and has two endogenous ligands, CCL19 and CCL21. Following binding of CCL21, 21 ± 4% of CCR7 is internalized in the HuT 78 human T cell lymphoma line, while 76 ± 8% of CCR7 is internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 83 publications
9
81
0
Order By: Relevance
“…1, indicating that ligand-receptor binding kinetics play important roles in DC chemotaxis in gradients of CCR7 ligands. At the highest ∇C tested (220 nM∕mm), the chemotactic response appeared to decrease for CCL19 but not CCL21; this may reflect differences in receptor availability due to CCR7 recycling only after binding CCL21 but not CCL19 (8,9,40). Such receptor recycling differences would lead to a higher apparent K D of CCL21 than CCL19 for binding CCR7, which is supported by the effective K D values estimated from fitting the data in Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…1, indicating that ligand-receptor binding kinetics play important roles in DC chemotaxis in gradients of CCR7 ligands. At the highest ∇C tested (220 nM∕mm), the chemotactic response appeared to decrease for CCL19 but not CCL21; this may reflect differences in receptor availability due to CCR7 recycling only after binding CCL21 but not CCL19 (8,9,40). Such receptor recycling differences would lead to a higher apparent K D of CCL21 than CCL19 for binding CCR7, which is supported by the effective K D values estimated from fitting the data in Fig.…”
Section: Resultssupporting
confidence: 64%
“…Both ligands have similar affinity to CCR7 (4,5), but drive different fates: CCL19 signaling leads to receptor internalization and temporal desensitization while CCL21 can signal from the cell membrane (6,9,40,44,45), a well described liganddependent process for G-protein-coupled receptors. This differential fate of activated CCR7 could lead to increased receptor density and signaling on the cell side dominated by CCL21 (46), consistent with our observation of increased DC response to CCL21 gradients above 50 nM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite CCL19 and CCL21 binding the same receptor, our studies and several others (7,50,51) showed that the cell perceives them as unique entities. In cross-desensitization studies, CCL19 inhibited CCL21 signaling but not vice versa (45,51), and despite similar G protein activation and calcium mobilization, differences were shown in receptor desensitization, internalization, and recycling (50)(51)(52)(53). In our direct competition assays between CCL19 and CCL21, opposing gradients of equal concentrations resulted in a biased response toward CCL19.…”
Section: Discussionmentioning
confidence: 85%
“…These results and others suggest that biased ligands or conditions that lead to selective activation of one pathway over the other will result in distinct physiological effects, possibly by stabilizing different "active" receptor conformations (33,34). There are indeed such examples of selective ligands; for example, CCL19 and CCL21 are two CCR7-specific endogenous chemokine ligands that are equally effective in their ability to activate G proteins, but only CCL19 can induce ␤-arrestin recruitment and ␤-arrestin-dependent ERK activation (44). Similarly, both ␤ 2 -adrenergic and parathyroid hormone receptors have been shown to have specific ligands that are biased toward either G protein-dependent or ␤-arrestin-dependent signaling (45,46).…”
Section: Discussionmentioning
confidence: 99%